2019
DOI: 10.1038/s41433-019-0596-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple subconjunctival conbercept injections as an adjuvant to the surgical treatment of pterygium: a prospective randomised comparative 6-month follow-up study

Abstract: Objective To evaluate the safety and efficacy of multiple subconjunctival injections of conbercept for pterygium patients after surgery. Methods As a prospective randomised interventional trial, 96 eyes from 96 patients with a tendency to recur were collected and divided randomly into conbercept and 5-fluorouracil groups on the 5th day after pterygium. All patients received three subconjunctival injections of conbercept (0.2 ml) or 5-fluorouracil (0.2 ml) on the 5th day (baseline), and 2 and 4 weeks postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These data indicate that Aflibercept was effective for the treatment of PM-CNV and could significantly improve the vision; however, it should be used on time to maximise the benefits of the drug. The safety of intravitreal anti-VEGF agents was also reported in many studies [30][31][32][33] . The RADIANCE, BRILLIANCE and LUMINOUS studies evaluated the use of ranibizumab for mCNV.…”
Section: Conbercept In the Treatment Of Choroidal Neovascularizationmentioning
confidence: 64%
“…These data indicate that Aflibercept was effective for the treatment of PM-CNV and could significantly improve the vision; however, it should be used on time to maximise the benefits of the drug. The safety of intravitreal anti-VEGF agents was also reported in many studies [30][31][32][33] . The RADIANCE, BRILLIANCE and LUMINOUS studies evaluated the use of ranibizumab for mCNV.…”
Section: Conbercept In the Treatment Of Choroidal Neovascularizationmentioning
confidence: 64%
“…Characteristics of the enrolled studies were shown in Table 1 . A total of 19 RCTs were included ( 12 26 , 30 , 32 , 36 , 38 ). There were 18 English articles and 1 Chinese articles.…”
Section: Resultsmentioning
confidence: 99%
“…Although our previous meta-analysis ( 2 ) and a recently published paper by Zhang ( 31 ) revealed that bevacizumab reduced recurrence after pterygium surgery, the finding wasn't conclusively supported by researches thereafter and the data just focused on bevacizumab. Some other anti-VEGF agents, including ranibizumab ( 32 35 ), conbercept ( 36 ), and aflibercept ( 37 ) also showed different efficacy in management of pterygium. Overall, the current evidence does not convincingly support the use of anti-VEGF in pterygium surgery ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted on 96 patients by giving them 3 subconjunctival injections of conbercept (with 0.2 mL) and 5 subconjunctival injections of 5-fluorouracil (with 0.2 mL). All the study data were collected from the fifth day after pterygium which is taken as a baseline to 2 to 4 weeks of postoperation . Sub tenon injections are yet another popular mode of administration.…”
Section: Strategies To Enhance the Ocular Bioavailability Of Proteins...mentioning
confidence: 99%